2017
DOI: 10.1017/s1049023x17005994
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic Accuracy of The Kampala Trauma Score using Estimated Abbreviated Injury Scale Scores and Physician Opinion

Abstract: Study/Objective: To determine the diagnostic accuracy of the Kampala Trauma Score in predicting Emergency Department outcomes in a limited diagnostics setting. Background: The Kampala Trauma Score (KTS) has been proposed as a triage tool for use in low-and middle-income countries (LMICs). This study aimed to examine the diagnostic accuracy of KTS in predicting emergency department (ED) outcomes, using timely injury estimation with Abbreviated Injury Scale (AIS) score, and physician opinion (PO). Methods: This … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(15 citation statements)
references
References 0 publications
0
15
0
Order By: Relevance
“…*Includes choking (1 patient), near-drowning (3), electrical injury (2), sexual assault (2) and non-specified (27). Deidentified data for patients aged less than 18 years were abstracted over a 4-year period from May 2011 to July 2015.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…*Includes choking (1 patient), near-drowning (3), electrical injury (2), sexual assault (2) and non-specified (27). Deidentified data for patients aged less than 18 years were abstracted over a 4-year period from May 2011 to July 2015.…”
Section: Discussionmentioning
confidence: 99%
“…They also allow the development of locally relevant and properly adapted metrics for patient-level risk adjustment and severity scoring, such as the Kampala Trauma Score (KTS) 27,28 . They also allow the development of locally relevant and properly adapted metrics for patient-level risk adjustment and severity scoring, such as the Kampala Trauma Score (KTS) 27,28 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The four prediction models we compared with the clinicians’ triage decisions were the Revised Trauma Score (RTS),5 the Glasgow Coma Scale, Age and Systolic Blood Pressure (GAP) score,2 the Kampala Trauma Score (KTS)6 and a prediction model previously published by us, here referred to as the Gerdin et al model 7. The rationale for studying these specific models was that RTS is commonly considered the gold standard of physiological trauma severity scoring,8 KTS has been shown to accurately predict inhospital mortality in both low-income, middle-income and high-income settings,9 10 and both GAP and the Gerdin et al model have been shown to predict short-term trauma mortality 8 11. The models considered age, systolic blood pressure, heart rate, Glasgow Coma Scale score, alert, voice, pain or unresponsive, respiratory rate and number of serious injuries (table 1).…”
Section: Methodsmentioning
confidence: 99%
“…14 Although trauma prognostication scores such as the KTS and RTS have been extensively compared to each other, 2 there are minimal data evaluating the clinical accuracy of the prolifically used TEWS as compared to trauma scores. 22,23 As a result, it is unclear whether there is additional benefit conferred by the use of injury-specific scores in LMIC settings for acutely injured patients beyond the use of standard triage approaches. This study compared the accuracy of the KTS, RTS, and TEWS in predicting mortality for injured patients at the emergency department (ED) of the Centre Hospitalier Universitaire de Kigali (CHUK), a tertiary care hospital in Rwanda that has implemented use of the TEWS in standard emergency care triage practice.…”
Section: Introductionmentioning
confidence: 99%